Evaluación de la distribución espacial y valor de uso de palmeras andinas en la concesión para conservación Alto Huayabamba - Díaz Salcedo, Katya Elízabeth (2014)
Peru has 25000 species of flora (1 O % of the world total), of which 30 % is endemic; 4440 species are used by the population by different purposes; nevertheless, the investigations realized in topics of this nature, they are not promoted like it must be.That is why, in the framework ofthe generation ofinformation ofthe concession to High Conservation Huayabamba river, the present study was carried out· called "Evaluation ofthe spatial distribution and val u e in use of palm trees in the Andean High Conservation Concession for Huayabamba river - SCF",In which there developed the study oftwo differentiated topics: the spatial distribution of Andean palms in the CCAH and the value of use for the population of out and inside the CCAH. After the evaluations, there were identified 04 kinds of Andean palms in Yungas ecosystem ofthe CCAH: Ceroxylon, Geonoma, Prestoea and Bactris,which are between 1750 and 2340 m.s.n.m.; ofwhich, only Prestoea and Geonoma are used in a direct way by ornamental ends by the population in situ. Likewise, there was evaluated the palms extraction method of the kind Ceroxylon on the part ofthe 'palmeros' (population ex-situ) in the frame ofthe celebration oftheHoly Week Bolivariana, which forms a part ofthe Nation Cultural Heritage. Key words: palm trees, Andean palms.